2015
DOI: 10.1021/acs.organomet.5b00439
|View full text |Cite
|
Sign up to set email alerts
|

PBiP Pincer Complexes of Platinum, Palladium, and Iridium Featuring Metal–Metal Bonds Synthesized by Oxidative Addition of Bismuth–Halide Bonds

Abstract: The compound BiCl(o-PPh 2 -C 6 H 4 ) 2 , PBiP-Cl, which in previous work had been shown to form complexes with pronounced M→Bi character, when metal(I) ions of group 11 or Pt II and Pd II ions were coordinated, behave differently in contact with late metal atoms in low oxidation states, known to easily undergo oxidative additions: Treatment of PBiP-Cl with M(PPh 3 ) 4 , with M = Pt, Pd, led to the formal insertion of M into the Bi−Cl bond to yield complexes [MCl(PBiP)]. Analogues PBiP-X with X = Br, I that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…[5m], [6h], For main‐group III and V elements as the anchor atom, it has been found that heavier atoms can act as stronger electron acceptors than their lighter homologues and that the binding type depends on the metal center itself and its oxidation state. [6n], [7b], Similar results were obtained for tripodal ligands bearing heavier main‐group IV elements as the anchor atom (Ge, Sn) bonded to group 11 metals. [7b] Nevertheless, there are indications that light main‐group III or V elements mainly act as Lewis acids[6e], [6l], or Lewis bases, respectively, whereas light main‐group IV elements (C and Si) bond to the metal center with predominantly covalent bond character.…”
Section: Introductionsupporting
confidence: 53%
“…[5m], [6h], For main‐group III and V elements as the anchor atom, it has been found that heavier atoms can act as stronger electron acceptors than their lighter homologues and that the binding type depends on the metal center itself and its oxidation state. [6n], [7b], Similar results were obtained for tripodal ligands bearing heavier main‐group IV elements as the anchor atom (Ge, Sn) bonded to group 11 metals. [7b] Nevertheless, there are indications that light main‐group III or V elements mainly act as Lewis acids[6e], [6l], or Lewis bases, respectively, whereas light main‐group IV elements (C and Si) bond to the metal center with predominantly covalent bond character.…”
Section: Introductionsupporting
confidence: 53%
“…Bearing in mind the scarcity of complexes with Pd ⋅⋅⋅ Bi interactions (apart from a cluster and a complex containing Pd−Bi metal bonds, only a Pd II →Bi complex of the above‐mentioned ambiphilic pincer ligand is known) the potential of Xan(PPh 2 )(BiPh 2 ) to bind Pd 0 was investigated. Therefore, a mixture of Xan(PPh 2 )(BiPh 2 ) and 0.25 equivalents of [Pd 2 (dba) 3 ] (dba=bis(dibenzylideneacetone)) was dissolved in tetrahydrofuran, and a color change from dark red to yellow was observed within a few minutes (Scheme ).…”
Section: Figurementioning
confidence: 99%
“…NBO analysis has been shown by many groups to be highly useful when analyzing weak to moderate bonding interactions such as ligand-metal donor-acceptor interactions 53,54 and metallophilic interactions. 10,41,[55][56][57] The monomers corresponding to 1(Me) (1-mon), 1-H(Me) Table 4, the Wiberg Bond Indices are in Table 5, and second-order perturbation energies in Table 6. Inspection of these three tables shows that each of the theoretical methods reproduces the same trends, and the methods behave as expected.…”
Section: -H(me)mentioning
confidence: 99%